Audiências virtuais criminais e direitos fundamentais : impactos aos principais destinatários da punição - Rheingantz, Mário Silveira Rosa (2021)
The present research aims to investigate if there are violations of fundamental rights produced by implementation of online hearings during the Covid-19 pandemic and, if so, to verify the impact to fundamental rights of people who are prosecuted in criminal courts, markedly provisionally imprisoned individuals. In order to do so, both the weakening of democratic institutions, and the processes ruled by the logic of efficiency and productivity were contextualized globally and nationally, based on the analysis of neoliberalism and its influence in punitive agencies. Furthermore, the pandemic was analyzed from a global and national point of view in light of neoliberal rationality and the context of Brazilian prisons during the Coronavirus pandemic. Finally, fundamental rights violated by online hearings were disclosed, as well as the real objectives, the legitimizing discourses, and the context of the pandemic as an element of escalation of unconstitutional violence with maintenance of provisional imprisonment. This escalation was based on the corporate govermentability of punitive agencies and on the crisis of measuring productivity during the pandemic in view of the suspension of in-person procedural acts. The research was developed through bibliographic review and analysis of regulations in abstract, as well as through analysis of data on the pandemic, especially on imprisoned people and on practices of punitive agencies. It was concluded that there is a series of violations of fundamental rights of defendants in online hearings, due to the logic of productivity and efficiency of the Judiciary Branch and other punitive agencies, and due to a legitimizing discourse about provisional imprisonment, which are some of the main reasons for the overpopulation of Brazilian penitentiary system